Oral Tradition : Idioms In Batak Toba’s Death Ceremony: A Semantics-Cognitive Study (International Journal of Education and Literature, 2024)
Batak Toba is one of the many ethnicities that exist in Indonesia as well as having unique cultures especially regarding to ceremonies and family especially when it comes to holding death ceremonies, in Batak Toba culture they have many. It is due to the fact that culturally and historically they are used to live under the circumstances of different status in the community. As modern as it gets, the death ceremony is still being held in its traditional ways with different ceremonies for different person according to how many families they have. Culture certainly influenced a lot in a community to the oral tradition by saying phrases and idioms that may sound different to another community from different background. This paper is intended to demonstrate the technical meanings of idioms that are commonly used in Batak Toba’s death ceremonies using semantics-cognitive study. This paper used a descriptive-quantitative approach with also the study of library study. The idioms that are written in this paper is searched from asking relatives who are of Batak Toba origin as well as from books, journals and several website articles.